ANALYSIS AS A SUBJECT OF FINANCIAL REPORTS AS OWNED BY ENTREPRENEURS AND LEGAL ENTITIES - Petković, Zdravka; Stojkanović, Denis (ACADEMIC REVIEW, 2021)
For any company, whether it is owned by legal entities or entrepreneurs, the analysis of financial statements primarily deals with the assessment of the financial condition of the company, as well as the management of working capital in the company. The main task of the analysis of financial statements in the company is the balance sheet, income statement, and cash flow statement, ie. change in capital. As for the business of receiving and processing financial reports in Serbia, they have a tradition of more than half a century, and they were published primarily in the service of social accounting, ie. to the Bureau of Accounts and Payments. Financial statements are a structural representation of business changes that occurred during the reporting period in order to provide information about the financial position, ie. financial success, as well as changes in the financial position of legal entities and entrepreneurs, which are very useful for making economic decisions of large users. In some cases, there may also be manipulation in the financial reports, that is, errors may occur, where auditors who carry out constant control deal with this.